Obstacles and Opportunities in Implementing Digital Marketing for MSMEs in Perlang Village - Muhammad Hayyi' Lana Alkhan; Ahmad Fauzi (JAMBE: Jurnal Akuntansi Manajemen Bisnis dan Ekonomi, 2024)
Abstract: This study aims to identify the barriers and opportunities in the implementation of digital marketing for Micro, Small, and Medium Enterprises (MSMEs) in Perlang Village. Using a qualitative approach and case study method, data were collected through in-depth interviews and observations of 10-15 MSME actors in the village. The results indicate that MSMEs in Perlang Village face various challenges, including limited access to technology and digital infrastructure, a lack of knowledge and skills in digital marketing, and uncertainty regarding the effectiveness of digital marketing strategies. Nevertheless, there are significant opportunities that can be leveraged, such as the growth of internet and social media users, support from the government and related institutions, and the potential of e-commerce as a marketing channel. This study concludes that to enhance the competitiveness of MSMEs, it is essential to improve access to technology, implement structured training programs, and provide ongoing support from the government. These recommendations are expected to assist MSMEs in Perlang Village in overcoming barriers and capitalizing on opportunities in digital marketing, thereby contributing to local economic growth. Keywords: Digital Marketing, MSMEs, Barriers, Opportunities, Perlang Village, E-commerce.